Qualitative Analysis of Corruption in Mining and Its Impact on Sustainable Development - Wibisana, Putu Arya; Widjojo, Suparto; Mudzakkir, Mohammad Fakhruddin; Amiati, Mia (RSF Conference Series: Business, Management and Social Sciences, 2024)
State management and oversight of natural resources is a constitutionally mandated responsibility. However, the mining extractive industry is often plagued by corruption, which hinders sustainable development efforts. This research investigates corruption within the mining extractive industry, focusing on cases related to mining business permits (IUP). Using a qualitative approach through a literature review, the study analyzes various corruption cases in the issuance of mining permits and examines relevant laws and regulations. The findings reveal that Indonesian mining regulations, grounded in the 1945 Constitution, mandate that natural resources be managed for public welfare. Law Number 4 of 2009 on Mineral and Coal Mining replaces the previous contract system with more transparent mining business permits overseen by both central and regional governments. This research underscores the need for regulatory improvements and a clearer delineation of authority to optimize natural resource management and prevent corrupt practices that undermine sustainable development efforts in Indonesia.